Penyidikan Tindak Pidana Pemalsuan Merek Spidol Snowman Berdasarkan Undang-Undang Nomor 15 Tahun 2001 Tentang Merek Oleh Polisi Daerah Riau - Pitri Aisyah; Rika Lestari; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Crimes regarding forgery or falsification is a crime abbreviated form of the crime in which an element of untruth or false state of something (an object), the things it looks from the outside as if true when in fact contrary to the truth. Regarding the rule of law and brand protection stipulated in Law No. 15 of 2001 on Marks. The author chose the study with Snowman marker object as a brand name items are forged with Snowmay markers, because this Snowman markers forgery case the most recent case handled by the Riau Police. Currently the case has SP3, or the forgery case does not proceed, because the parties have to take the path of peace. In the stages of the investigation, the expert witness presented by investigators, stating that the case of counterfeiting markers Snowmay into markers Snowman, was not included into the brand counterfeiting, because the difference between the brand name markers.Issues examined in this study are: First, Do suspicion of counterfeiting markers Snowman become markers Snowmay brand counterfeiting is a criminal offense? Second, How is the investigation of criminal trademark counterfeiting markers Snowman by Act No. 15 of 2001 on Marks by Riau Regional Police ?, What considerations Ditreskrimsus Riau Police investigators claimed that brand counterfeiting markers Snowman is a forgery under Article 91 of Law No. 15 of 2001 Trademark by Riau Regional Police?This type of research is the study of law Sociological. Source data used are primary data and secondary data, data collection techniques. obtained from interviews and literature study. In this study the authors used a qualitative analysis, in drawing conclusions using inductive method of thinking. Results from this study is the first, suspicion of fraud markers Snowman become markers Snowmay a criminal offense of counterfeiting brand is something of a misnomer, because there is a difference in form, name, layout and mentions between markers Snowmay and markers Snowman is the fact that the allegation of forgery brand is mistaken , Second, the investigation of cases of counterfeiting markers Snowmay and markers Snowman become expert examination has been to such a degree, but the case eventually stopped after the complainant revoke its report. In this case the investigator using Article 91 of Trademark Law. Third, consideration Riau Police investigators claimed that brand counterfeiting markers Snowman is a forgery because of a report from the complainant who use Law No. 15 of 2001 on Marks. Suggestions from authors First, investigators must be careful in determining the allegation in a case of forgery of brands Second, in the implementation of the investigation of alleged cases of counterfeit brand Snowman goes wrong, because this case is not counterfeit brand, Third, investigators must be careful in determining the elements of a criminal offense.Keywords: Counterfeit Brand-Markers Snowman-Ditreskrimsus